2018
DOI: 10.1016/j.jvir.2017.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Guidelines for Mesenteric Angioplasty and Stent Placement for the Treatment of Chronic Mesenteric Ischemia

Abstract: The membership of the Society of Interventional Radiology (SIR) Standards of Practice Committee represents experts in a broad spectrum of interventional procedures from the private and academic sectors of medicine. Generally, Standards of Practice Committee members dedicate the vast majority of their professional time to performing interventional procedures; as such, they represent a valid broad expert constituency of the subject matter under consideration for standards production.Technical documents specifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 78 publications
0
49
1
4
Order By: Relevance
“…Due to historically predominant ostial location of celiac or SMA stenotic or occlusive disease, angioplasty alone is associated with elastic recoil and usually necessitates stent placement. Pooled analysis of multiple studies showed technical success rate of angioplasty and stent placement to be significantly higher, 85–94% whereas for angioplasty alone to be 65–79% . Oderich et al reported 7% major complication rate in 156 patients who underwent mesenteric artery angioplasty and stenting, mostly (98%) with balloon expandable bare metal stents (BMS).…”
Section: Discussionmentioning
confidence: 99%
“…Due to historically predominant ostial location of celiac or SMA stenotic or occlusive disease, angioplasty alone is associated with elastic recoil and usually necessitates stent placement. Pooled analysis of multiple studies showed technical success rate of angioplasty and stent placement to be significantly higher, 85–94% whereas for angioplasty alone to be 65–79% . Oderich et al reported 7% major complication rate in 156 patients who underwent mesenteric artery angioplasty and stenting, mostly (98%) with balloon expandable bare metal stents (BMS).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 For atherosclerotic CMI, endovascular revascularization with PTA and stent placement is now widely accepted as a preferred therapeutic alternative to open surgical approaches in patients with ostial or proximal mesenteric arterial obstruction without bowel infarction. 10,19 Compared with endovascular revascularization, most open surgical procedures still result in higher, long-term patency rates in the published literature, and as a result, patients younger than 50 years often undergo open surgery, and older patients often undergo PTA and stent placement. 16,18,20,21 Stent placement in combination with PTA offers higher rates of technical success than with PTA alone for calcific atherosclerotic lesions.…”
Section: Endovascular Managementmentioning
confidence: 99%
“…23 Distal mesenteric embolization and mesenteric vessel dissection has been reported in 0 to 11% and 0 to 6% of cases, respectively. 19,[24][25][26] Acute bowel infarction necessitating resection occurred in 1 to 4% of cases. 23,27 In MALS, contemporary literature describes laparoscopic and robot-assisted approaches as the developing standards for definitive treatment, although open surgical approaches are still widely used.…”
Section: Endovascular Managementmentioning
confidence: 99%
See 2 more Smart Citations